Febril konvülsiyon geçiren çocukların demografik ve klinik özelliklerinin incelenmesi / The investigation of the demographic and clinical characteristics of children with febrile convulsion - ABDİLLAHİ, FATOUMA KHALİF (Bezmialem Vakıf University, 2017)
Febrile convulsion is characterized by a convulsion during a febrile disease of children between 1 months to 6 years without a history of afebrile convulsion, excluding CNS infection or any other possible etiology such as electrolyte imbalance, metabolic disturbance, intoxication or trauma. Febrile convulsions (FC) are the most common type of convulsions in childhood. Recurrences are frequent in FC. The children who experience a 2nd FC episode constitute 30-40%. In this study; 310 children with FC admitted to Bezmialem Vakif University, Pediatrics neurology clinic between 2013-2016 were included. The demographic features, recurrence and epilepsy risks and efficacy of different type of therapies were evaluated. It is aimed to retrospectively analyze the demographic and clinical characteristics of children between 6 months and 5 years of age and to analyze factors that may be related to febrile convulsion. The Male/female ratio was 1.3/1. An eleven (3,4%) of 310 had history of prematurity, 4 (1,4%) of 310 perinatal asfixia. The age of first FC was between 6-72 months (average age 25 months). FC was most frequent below 2 years of age (53%).Upper respiratory tract infection was the most frequent etiology (85%). Family history of febrile convulsions in 61 cases (19.6%) in father-mother and febrile convulsions in 42 cases in sister-brother (13.6%).Simple type first FC constitute 90,3%, whereas complex 9,7%. In 94,4% of patiens FC were of generalized-tonic-clonic type. Two hundred and fourteen patiens (65,8%) had reccurence. Epileptiforms disorders was not detected in cases who underwent electroencephalogram. One hundred and eleven cases (35.8%) underwent profilatic treatement. Of these, 55 cases (17.8%) receveid valproic acid and 15 cases (4,8%) long term oral phenobarbital. İntermitent rectal diazepam was given in 40 cases (%13,2). Recurence was seen in 1 out of 15 cases (6,6 %) after the onset of phenobarbital treatement, and in 13 out of 55 cases (23,63%) after valproic treatement. As a result, it was concluded that is very important to follow up patients with FC, which has good clinical course, because of high recurrence. Our study has been shown to be in accordance with literatüre.
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Child Health and Diseases, Istanbul, 2017
Keywords: Çocuk Sağlığı ve Hastalıkları = Child Health and Diseases